The Implementation of No-Smoking Area Policy to Improve Community Health and its Relationship to the Country’s Pharmaceutical Policy: A Study in Semarang City in Indonesia - Kusworo . (Journal of Global Pharma Technology, 2020)
Cigarettes smoking in Indonesia is rampant despite of its harmful effects on human health and the environment, which calls for government intervention. This study examines the implementation of the No-Smoking Area Policy in increasing the degree of public health in Semarang city by focusing on the inhibiting factors of the policy, and the efforts taken by government to overcome obstacles in its implementation. The study used qualitative research with action research method. Data collection techniques were semi-structured interviews, observations, and documentation study. The data analysis technique used was the triangulation method. Findings indicate that the No-Smoking Area policy has been implemented in Semarang city but it is still in the socialization stage. There are several obstacles in its implementation that still need proper handling by the Semarang City local government, especially its health office, notably the program’s implementation, compliance and responsiveness, and resources involved, including its relatedness to the pharmaceutical policy implementation. The efforts made by the city government to overcome the obstacles in the implementation of the policies include providing guidance to the entire staff of Semarang City Health Center, socialization of the policy to the community through community health units, making No-Smoking signs, stickers, leaflets, and banners, and performing activities during the celebration of the world’s no-tobacco day. Keywords: Tobacco, Smoking and No-Smoking Area, Policy Implementation, Pharmaceuticals and Narcotics, Public health.